Integration of real-time hardware and TCP/IP communications for teleoperation systems - Ollin, Peñaloza-Mejía (2007)
This paper describes the development of an experimental platform for robotic teleoperation via Internet. It is obtained by adding Internet capabilities to an industry-standard DSP board, available in many universities and research centers.